Building scale centralized and decentralized decision-making in the Iraqi Federation of Central Basketball. - Mohammed , Safad; Aziz, Khalid (Humanities Journal of University of Zakho, 2020)
The research aims to: Buildingscalecentralized and decentralizeddecision-makingintheIraqi Federationof CentralBasketballin Iraq. Identify the factors Order centralized and decentralized decision-making at the Iraqi Central basketball from the perspective of working in branch of sports federations subsidiary. Was used descriptive method in a way the survey to its relevance and the nature of research, and consisted of the sample of two parts, the first section included a sample construction of which there were (108) individual factor in branch of sports federations of basketball in Iraq, while the included second section sample application which numbered (40) individual factor in branch of sports federations of basketball in Iraq. Means of data collection: A tool to measure the central and decentralized decision-making: The researcher built a measure of centralization and decentralization in decision-making with the Iraqi Federation of basketball after the conditions are met the scientific standard has included the scale (20) paragraph. Data were treated statistically using: The arithmetic mean, standard deviation and the law of percentage and Pearson’s samples and analysis of variance and the coefficient Alpha and fair Gateman equation was used Spearman Brown. The main conclusions as follows: Validity of scale in centralized and decentralized decision-making in the measurement of the nature of the decision-making to the Iraqi Union of basketball. The researcher concluded that the sample individuals agree to their participation in decision-making process of the Iraqi Union of basketball, and that the decision-making process of these are centralized in some respects while increasing the degree of decentralization in other aspects of it. In light of the results the researcher presented a number of recommendations including: the application of scale in centralized and decentralized decision-making sports organizations across Iraq. the researcher recommends the need for continuity of the Iraqi Federation of Basketball in supporting the trend towards decentralization in decision-making, by giving workers in branch of sports federations of the necessary powers to carry out their duties flexibly and effectively, which leads to the lifting of the level of job satisfaction. The Researcher administrative leadership in the Iraqi Federation of Basketball to grant workers in branch of sports federations, letters of thanks to meet their distinctive because it would contribute to raising the morale and makes them dissatisfied with their work, such as setting specific criteria through which the nomination of the Working perfect in every sports association on an annual basis in order to reward, Develop allowances for workers in branch of sports federations for basketball in Iraq. Work to increase the financial allocations for workers in branch of sports federations for basketball in Iraq in order to fit with their efforts, and not to delay the disbursement dates. The researcher proposed the following two: A comparative study in centralized and decentralized decision-making of the Iraqi Federation of basketball with other unions. 2. Working on a law to full-time workers in the sports federations to carry out their tasks in unions while retaining their rights official in the institutions in which they work, in order to have a chance creativity, and provide services in both functions.